Obsession For The Return Of The Lost Daughter In David Auburn's The Girl In The Park Movie: A Psychoanalytic Approach - Rofiah, Rofiah (2012)
The study focuses on Julia's Obsession to return her lost daughter. It is reflected in the major character of The Girl in the Park viewed from psychoanalytic approach. The object study is to explore the obsession of Julia to return her lost daughter into her life. The type of this study is qualitative study. In this study, the researcher uses two data sources namely primary and secondary data. The primary data source and object of the study are The Girl in the Park movie itself. Meanwhile the secondary data are any literature related with the study. The technique of data analysis in this study is descriptive method. The result of the study shows the following conclusion. Firstly, based on the structural analysis, it is evident that in this movie David Auburn is delivering a message that it is usually hard for people to accept reality of losing one that they love. Secondly, based on psychoanalytic analysis, it is apparent that in this movie, David Auburn illustrates a psychological phenomenon in which an individual experiences obsession to bring her lost child back to her.